Pengaruh Loan To Value (LTV) dan Shock Variabel Makroekonomika terhadap Industri Properti di Indonesia - Yustina Irmiyanti Mamir Tanar; Fransina W. Ballo; Cicilia A. Tungga (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to determine the influence of Loan To Value (LTV), BI Rate and Exchange Rate on Residential Property Sales. This type of research is quantitative research with secondary data in the form of Loan To Value, BI Rate, Exchange Rates and Residential Property Sales data. The data analysis technique used is SPSS. .The results of this research show that LTV, BI Rate and Exchange Rate simultaneously influence Residential Property Sales with a significance of 0.004 < 0.05. Meanwhile, partially LTV has a positive effect on Residential Property Sales with a significant value of 0.897, BI Rate has a positive effect on Residential Property Sales with a significant value of 0.173 and the Exchange Rate has a positive effect on Residential Property Sales with a significant value of 0.001. With the results achieved, namely LTV, BI Rate and Exchange Rate, they play an important role in the sale of Residential Property. For related agencies, it is better to improve their performance to improve the quality of Residential Property Sales.